Regulation of Lignin Biosynthesis and Its Role in Growth-Defense Tradeoffs - Xie, Meng; Zhang, Jin; Tschaplinski, Timothy J.; Tuskan, Gerald A.; Chen, Jin-Gui; Muchero, Wellington (Frontiers in Plant Science, 2018)
Plant growth-defense tradeoffs are fundamental for optimizing plant performance and fitness in a changing biotic/abiotic environment. This process is thought to involve readjusting resource allocation to different pathways. It has been frequently observed that among secondary cell wall components, alteration in lignin biosynthesis results in changes in both growth and defense. How this process is regulated, leading to growth or defense, remains largely elusive. In this article, we review the canonical lignin biosynthesis pathway, the recently-discovered tyrosine shortcut pathway, and the biosynthesis of unconventional C-lignin. We summarize the current model of the hierarchical transcriptional regulation of lignin biosynthesis. Moreover, the interface between recently identified transcription factors and the hierarchical model are also discussed. We propose the existence of a transcriptional co-regulation mechanism coordinating energy allowance among growth, defense and lignin biosynthesis.